NEWS CONTENT UNDER DIGITAL GLOBALIZATION - Oksana L. Servetnik (Вестник Северо-Кавказского федерального университета)
The article deals with the issue of circulating illegal news content in the global computer networks through social networks and the related new ways for manipulating public opinion.